Potato tracheomycosis development through the climat aridization - Andriychuk, T. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2025)
Goal. To evaluate the damage of potatoes by tracheomycoses and to identify the most common tracheomycotic diseases, to study the symptoms of diseases, to analyze and clarify their etiology.Methods. The research was conducted during 2022—2023 at the Ukrainian Research Station of Plant Quarantine of the Institute of Plant Protection, using field (survey of potato plantations to identify and establish the spread of tracheomycotic diseases of potatoes) and laboratory (identification of pathogens) methods.Results. Studies conducted during 2022—2023 showed that tracheomycosis is a significant disease of potatoes. The main pathogens that dominated the potato plantations were the fungi Fusarium oxysporum Schl., Verticillium albo-atrum Reinke and Berthold; Colletotrichum coccodes (Wallr.) Hughes. The first manifestations of wilting, both in 2022 and 2023, were observed in the second decade of June in the budding-flowering phase. The number of affected bushes of different varieties ranged from 11 to 25%. In the second half of the growing season, the number of affected bushes increased to 35%, each of them had several dried stems. By the end of the potato growing season, wilt damage of various etiologies had already reached 65—75%. The surveys and analysis of the selected samples showed that Fusarium wilt was the most widespread in the research area in 2022 and 2023. The disease prevalence in 2022 for different varieties was 27.2—36.7%. Verticillium wilt was less common, the number of affected bushes of the studied varieties was 10.5—22.1%. In the third decade of July, symptoms of anthracnose were detected. The disease prevalence in 2022 was 14.3—25.3%. A similar situation was observed in 2023 with the dominance of Fusarium wilt, the prevalence of which was 31.7—45.3%.Conclusions. Changes in climatic conditions have led to a significant spread of wilt diseases (Fusarium wilt, verticillium wilt, anthracnose) of potatoes and now pose a threat to the production of quality seed and food potatoes.